Comparative analysis of microelectromechanical inertial measurement units of various manufacturers for human motor activity monitoring - G. A. Fofanov (Омский научный вестник, 2020)
In this paper, we compare microelectromechanical inertial measuring modules that can be used to record the motor activity of a person. The comparison involved sensors with nine degrees of freedom of the lower price category. Such parameters as the value of noise at rest, the average deviation of the measured data from the true values, the average value of gyro drift under influence of external factors and without, built-in sensor capabilities, and ease of setup are evaluated. Based on the comparison data, the most suitable inertial measuring module for recording a person’s motor activity is selected.